The Cardioprotective Effects of Sida rhombifolia Leaf Extract in Cardiac Injury Rat Model - Wangiyana, Ni Komang Ayu Swanitri; Wasityastuti, Widya; Nugroho, Justinus Putranto Agung; Rosada, Marwan; Setiawan, Jajar; Wahyuni, Tutik Sri (Iraqi Journal of Science, 2025)
High-fat diets (HFD) and high-sucrose diets increase the risk of cardiometabolic diseases. The combination of the two diets reflects the Western dietary trend. The mortality due to cardiovascular disease is still high. Therefore, new treatment options are urgently needed to address the issue, such as through the exploration of medicinal plants. This study aimed to examine the effects of Sida rhombifolia (SR) leaf extract on IL-6 mRNA expression, histopathological findings, and troponin I level in the heart of rats induced by a high-fat-sucrose diet and carbon tetrachloride (CCl4). Forty male Sprague Dawley rats were randomly divided into five equal groups: negative control (C-), positive control (C+), and three groups given SR extract with the following doses: SRE1 (100mg/kgBW), SRE2 (200mg/kgBW), and SRE3 (400 mg/kgBW). The C+ and the extract groups were treated with the high-fat-sucrose diet (32.2% fat content, 10% sucrose) and CCl4 injection (0.4 mg/kg body weight). All treatments were conducted for 12 weeks. The expression of IL-6 in the C+ was significantly lower than C-, and only the SRE2 expressed a significantly higher IL-6 than the C+. A higher degree of inflammation was also observed in the C+ compared to the C-, while the SRE2 had a significantly lower degree of inflammation than the C+ group. The myocardial tissue in the SRE2 and SRE3 groups also showed less fibrosis. There was no difference in plasma troponin I levels among groups. We collectively found that the SR extract provides cardioprotection by altering the degree of myocardial inflammation and IL-6 mRNA expression in rats with cardiac injuries.